Wieś – miasto. Opozycje, antagonizmy, splątane narracje - Wieruszewska, Maria (Zeszyty Wiejskie, 2016)
The subject of analysis are – various images, views, perceptions, meanings and interpretations of the countryside and towns in Europe. The terms, words and notions used in the description have a character of historical and spatial relations. The author compares the views of towns and countryside from the beginning of industrial era to nowadays. Examples quoted in the article and situations described by literature, also expressed in sociological, economical papers, as well as in popular opinions, have showed the changing statements in the matter. She draws the attention to the strong points of the village and the rural community. The statements in which towns (metropolitan areas) are considered the “natural” and the only direction for the social development are discussed in the paper.